ANALISIS KECELAKAAN KERJA DENGAN MENGGUNAKAN METODE HAZARD AND OPERABILITY STUDY (HAZOPS) DI PT MANDIRI JOGJA INTERNASIONAL - Titin Isna Oesman; Endang Widuri Asih (PROSIDING SNAST, 2018)
PT Mandiri Yogyakarta International (MJI) or by any other name is the industry that produces Bucini handbags, shoes, wallets, belts, and other accessories with many variations, the manufacture of a product from raw material cow leather. In production activities using equipment and machinery which can cause accidents. Therefore in this study carried out a strategy to manage the occurrence of potential dangers in PT. MJI. Research conducted at the work stations cutting and sewing the risk of accidents is high 13 (thirteen) times for cutting a year and 14 (fourteen) times for sewing in a year. Identification of the potential dangers of using methods of Hazard and Operability Study (HAZOPS) based on the processes that occur in PT. MJI. So the accident happened can be minimised or even anccident zero.The results of research on the production process it was found that the source of potential hazard is a condition of the work environment, the pieces of the cutter, the attitude of workers scattered, cable, hot air. From calculations using the method of hazops potential dangers exposed blades and needles becomes a top priority with Severity Category 3 (three), Score 4 (four), the Frequency Level B Score 4 (four), Risk Rating Number 8 (eight) and index Risk 3B. Based on the potential hazard that may occur then advised the company that it may provide training accident and work safety (K3) for all employees, the use of protective tools themselves, and there are supervisors when employees work.